Pengaruh Technology Acceptance Model Terhadap Minat Mahasiswa Unisba Dalam Menggunakan Shopee Paylater - Nesta Amalia Apriliani Deden Rahmat (UNISBA Press, 2023)
The research was conducted with the aim of examining the effect of the TAM variable seen from the Perspective of perceived usefulness, Perceived ease of use, Behavioral intention to use and Actual to use partially on Unisba students' interest in using the shopee paylater. This is because the number of E-commerce users in Indonesia continues to increase every year, the number of system users' paylater payments has also increased from the previous year. This study uses a quantitative approach or method, the population used is the Shopee Paylater application users. Data collection techniques were carried out by distributing questionnaires to 100 respondents online and analyzed. The data analysis technique used in this study is the OLS regression. The results of this study indicate that the TAM Perspective variables perceived usefulness, Perceived ease of use, Behavioral intention to use and Actual to use have positive and significant values for Unisba students' interest in using Shopee Paylater. Abstrak. Penelitian dilakukan dengan tujuan untuk menguji pengaruh dari variabel TAM dilihat dari Perspektif perceived usefulness, Perceived ease of use, Behavioral intention to use dan Actual to use secara parsial terhadap minat mahasiswa unisba dalam menggunakan shopee paylater. Hal ini dikarenakan banyaknya pengguna E-commerce di Indonesia terus meningkat setiap tahun, jumlah pembayaran paylater pengguna sistem juga meningkat dari tahun sebelumnya. Penelitian ini menggunakan kuantitatif pendekatan atau metode, populasi yang digunakan adalah pengguna aplikasi Shopee Paylater. Teknik pengumpulan data dilakukan melalui penyebaran kuesioner kepada 100 responden secara online dan dianalisis. Teknik analisis data yang digunakan adalah dalam penelitian ini adalah regresi OLS. Hasil penelitian ini menunjukkan bahwa variabel TAM Perspektif perceived usefulness, Perceived ease of use, Behavioral intention to use dan Actual to use bernilai positif dan snifikan terhadap Minat mahasiswa unisba dalam menggunakan Shopee Paylater.